2022
DOI: 10.3389/fvets.2022.822367
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol Improves Follicular Survival and Development During in vitro Culture of Goat Ovarian Tissue

Abstract: This study evaluated the effects of different concentrations (10, 20, or 40 μM) of eugenol (EUG 10, EUG 20, or EUG 40), ascorbic acid (50 μg/mL; AA) or anethole (300 μg/mL; ANE 300) on the in-vitro survival and development of goat preantral follicles and oxidative stress in the cultured ovarian tissue. Ovarian fragments from five goats were cultured for 1 or 7 days in Alpha Minimum Essential Medium (α-MEM+) supplemented or not with AA, ANE 300, EUG 10, EUG 20 or EUG 40. On day 7 of culture, when compared to ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 47 publications
(61 reference statements)
2
11
0
Order By: Relevance
“…Unlike H3K9me3, which is involved in gene silencing, increased H3K4me3 is associated with gene expression activation (Ren et al, 2022;Yu et al, 2018), which suggests that in the present study, the anethole treatment promoted a shift from a repressive to a more active chromatin state. Previous observations by our group revealed that anethole increased H3K4me3 fluorescence intensity in early PA follicles included in ovarian tissue grown in vitro compared with follicles grown in vivo (Silva et al, 2022). Similar results were obtained by using ascorbic acid, which altered H3K4me3 fluorescence intensity without altering H3K9me3 fluorescence intensity during in vitro maturation of porcine COC (Yu et al, 2018).…”
Section: Ros Levels In the Spent Mediumsupporting
confidence: 86%
See 4 more Smart Citations
“…Unlike H3K9me3, which is involved in gene silencing, increased H3K4me3 is associated with gene expression activation (Ren et al, 2022;Yu et al, 2018), which suggests that in the present study, the anethole treatment promoted a shift from a repressive to a more active chromatin state. Previous observations by our group revealed that anethole increased H3K4me3 fluorescence intensity in early PA follicles included in ovarian tissue grown in vitro compared with follicles grown in vivo (Silva et al, 2022). Similar results were obtained by using ascorbic acid, which altered H3K4me3 fluorescence intensity without altering H3K9me3 fluorescence intensity during in vitro maturation of porcine COC (Yu et al, 2018).…”
Section: Ros Levels In the Spent Mediumsupporting
confidence: 86%
“…However, an increase of H3K4me3 in the regulatory regions of STAR, CYP17, and CYP19A1 in GC (Bahrami & Maleki, 2019;Sha, Jiang, et al, 2020), and genes related to survival and growth in oocytes and suppression of oxidative stress (Ren et al, 2022;Yu et al, 2018) et al, 2015), might also be involved. Previous work from our laboratory has suggested that the antioxidant effects of anethole on PA and EA follicles in culture may involve KDM genes and H3K4me3 (Sá et al, 2017;Silva et al, 2022). In addition, the increase in H3K4me3 herein observed might have been a result of an increase in the expression of the CXXC finger 1 protein (CFP1), a DNA-binding subunit of the histone methyltransferase SETD1.…”
Section: Ros Levels In the Spent Mediummentioning
confidence: 73%
See 3 more Smart Citations